Influence of initial particle size on the magnetostriction of sintered cobalt ferrite derived from nanocrystalline powders - Mohaideen, Kamal Khaja; Joy, Pattayil Alias (Journal of Magnetism and Magnetic Materials, 2013)
The role of initial particle size on the magnetostriction coefficient of sintered cobalt ferrite derived from nanocrystalline powders is studied. Nanoparticles of cobalt ferrite with different sizes in the range 3-80 nm are synthesized by an autocombustion method using metal nitrates and glycine. It has been observed that the initial particle size of the starting powders has a strong influence on the magnetostrictive behavior of sintered cobalt ferrite. Highest magnetostrictive strain and strain derivative are obtained for sintered ferrite derived from nanoparticles of size < 5 nm. The results show that higher magnetostriction coefficient for sintered cobalt ferrite can be achieved by compacting nanocrystalline particles of very small size. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cobalt ferrite; magnetic properties; Magnetostriction; Microstructure; Nanocrystalline; Particle size